2017
DOI: 10.1002/smll.201702571
|View full text |Cite
|
Sign up to set email alerts
|

Superior Self‐Powered Room‐Temperature Chemical Sensing with Light‐Activated Inorganic Halides Perovskites

Abstract: Hybrid halide perovskite is one of the promising light absorber and is intensively investigated for many optoelectronic applications. Here, the first prototype of a self-powered inorganic halides perovskite for chemical gas sensing at room temperature under visible-light irradiation is presented. These devices consist of porous network of CsPbBr (CPB) and can generate an open-circuit voltage of 0.87 V under visible-light irradiation, which can be used to detect various concentrations of O and parts per million… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
97
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 47 publications
0
97
0
Order By: Relevance
“…We have recently reported one of the first self‐powered chemical sensor for the detection of volatile organic compounds (VOCs) using visible light‐activated inorganic halide perovskites at room temperature. [ 12 ] Notably, we have observed that the metal halide perovskite plays a dual role as both the active gas sensing material and as effective environment light harvester, capable of self‐powered sensing without any applied external bias. [ 12 ] Although such self‐powered chemical sensors are progressing rapidly, [ 4,5,12 ] a major challenge is achieving excellent performance for certain gas and their self‐powered use in dark conditions when light irradiation is temporarily unavailable.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…We have recently reported one of the first self‐powered chemical sensor for the detection of volatile organic compounds (VOCs) using visible light‐activated inorganic halide perovskites at room temperature. [ 12 ] Notably, we have observed that the metal halide perovskite plays a dual role as both the active gas sensing material and as effective environment light harvester, capable of self‐powered sensing without any applied external bias. [ 12 ] Although such self‐powered chemical sensors are progressing rapidly, [ 4,5,12 ] a major challenge is achieving excellent performance for certain gas and their self‐powered use in dark conditions when light irradiation is temporarily unavailable.…”
Section: Figurementioning
confidence: 99%
“…[ 12 ] Notably, we have observed that the metal halide perovskite plays a dual role as both the active gas sensing material and as effective environment light harvester, capable of self‐powered sensing without any applied external bias. [ 12 ] Although such self‐powered chemical sensors are progressing rapidly, [ 4,5,12 ] a major challenge is achieving excellent performance for certain gas and their self‐powered use in dark conditions when light irradiation is temporarily unavailable. [ 5,12 ] To address the need of continuous power supply, energy storage components, such as lithium ion batteries and supercapacitors, have been integrated with perovskite solar cells to achieve fully self‐powered devices, such as photo‐supercapacitor and perovskite photovoltachromic supercapacitor.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Some ILs are known to form a gel when suspended in eco‐friendly polymers, including poly(vinyl alcohol) (PVA), poly(ethylene oxide) (PEO), and poly(ethylene glycol) (PEG) . Owing to such characteristics, the use of ILs is not limited to the electrolyte of high capacity batteries but also applicable to functional devices such as photovoltaics, energy storages, and tactile sensors . Nonetheless, some ILs have toxicity or nonbiodegradability that hinder their disposable use.…”
Section: Introductionmentioning
confidence: 99%